(untitled) (Journal of Laboratory Animal Science, 2024)
The time points of development of laboratory animal-based research and establishment of societies/associations for laboratory animal science differ in the Asian part of the world. Some of the Asian countries do not have their own associations and they are in the process of establishing them. In this context, we conceptualized the idea through this article to provide an overview on initiation of laboratory animal-based research and establishment of associations or societies in several different Asian countries.